Is the Animal Liberation Front morally justified in engaging in violent and illegal activism towards animal farms?. Issue 2 (3rd May 2016) - Cordeiro-Rodrigues, Luís
ABSTRACT: The Animal Liberation Front (ALF) is an activist group, mainly focused on violent and illegal direct action, including destruction of property, the rescuing of animals and the clandestine filming of animal cruelty on animal farms. Here, I engage with three arguments that are often raised against the ALF's actions, namely these actions are not morally justified because: (a) they are not measures of last resort; (b) they are excessively violent and do not discriminate targets; and (c) they have no reasonable probability of success. I contend that clandestinely filming animal cruelty is morally justified, the destruction of property is not and that rescuing animals is morally justified, if the ALF incorporates some changes as to how this is done.